Zuruf: Landschaft aus ökonomischer Sicht - Zimmermann, Horst (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
This paper is a response to the special issue on the social constitution of cultural landscapes in “Raumforschung und Raumordnung”. It adopts an economic perspective that provides a sober-minded look at the issue of cultural landscape and reveals the economic significance of landscape. According to this perspective, (cultural) landscapes are characterised by features which are typical of public, regional, and scarce goods. From this it is argued that scarcity necessitates political intervention to ensure maximum benefits of use for the electorate.
Keywords: Cultural landscape; Economy; Public good; Landscape assessment